PERAN GURU BIMBINGAN KONSELING DALAM MEMBENTUK PRIBADI YANG UNGGUL PESERTA DIDIK MTs AL KAMAL TARUB TEGAL - roikhatul jannah (JCOSE Jurnal Bimbingan dan Konseling, 2019)
A superior person is a human condition as an individual who has better qualities than others. With a superior personality possessed, someone's life will look better than others in terms of their personality and are respected by many others. One form of this superior person is noble character, noble character is a good action (behavior / trait) that has been deeply embedded in one's soul so that it makes his personality good too. This study aims to find out the superior personal forms, services used by the Counseling Guidance teacher, and the time used by the Counseling Guidance teacher in shaping the personality of the students. This type of research is qualitative research using observation instruments, in-depth interviews and documentation. Based on the results of the study, it can be concluded that the role of the counselor proved to be able to form the superior personality of MTs Al Kamal Tarub students. Counseling activities conducted by Guidance Counseling teachers at MTs Al Kamal Tarub have had a good impact, this can be seen from the students' personalities at MTs Al Kamal Tarub Tegal.